PENGARUH ENDORPHIN MASSAGE TERHADAP INTENSITAS NYERI PUNGGUNG BAWAH IBU HAMIL TRIMESTER III - Ayu Handayany, Diah; Mulyani, Sri; Nurlinawati, Nurlinawati (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2020)
At present only about 20% of patients who are truly cured through medication action and in the health world are developing alternative methods to reduce maternal suffering during pregnancy and childbirth. Endorphin massage is the best nonpharmacological therapy to deal with these problems. The purpose of this study is to determine the effect of endorphin massage on the intensity of lower back pain in third trimester pregnant women at the working area of Putri Ayu Health Center, Jambi City. The type of research used was a Pre-experimental study with One Group Pre-test Post-test Design. Samples were taken from populations that fulfilled the inclusion criteria as many as 20 pregnant women . The sampling technique used was Accidental Sampling. The instrument used was an SOP of endorphin massage technique and the Numeric Rating Scale pain observation sheet. The results showed before endorphin massage, almost half (45%) of the all pregnant women had severe pain and after endorphin massage none of the respondents (0%) had severe pain. The results of the Wilcoxon sign rank test with α = 0.05 were obtained Asymp. Sig.= 0,000 showed there was an effect of endorphin massage on the intensity of lower back pain. Endorphin massage can inhibit pain transmission through skin stimulation that releases endorphin compounds that stop pain impulses. therefore, there is an effect of endorphin massage on the intensity of low back pain in third trimester pregnant women in the working area of ​​the Putri Ayu Public Health Center in Jambi